2021
DOI: 10.1021/acschemneuro.1c00130
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Adenosine Receptors by Hops and Xanthohumol in Cell Cultures

Abstract: Adenosine receptors (ARs) have been involved in neurodegenerative diseases such as Alzheimer disease, where oxidative stress contributes to neurodegeneration and cell death. Therefore, there is increasing interest in developing antioxidative strategies to avoid or reduce neurodegeneration. We have previously described that different beer extracts modulate ARs and protect glioma and neuroblastoma cells from oxidative stress. The present work aimed to analyze the possible protective effect of hops (Humulus lupul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…First, a study of the cell viability of C6 and SH-SY5Y cells in the presence of different concentrations of Xn was conducted in order to establish a proper concentration that has no severe toxicity to these cell lines. Previous results of our group showed no significant effect of 10 µM Xn in these cell lines; therefore, 5 and 15 µM Xn were tested [ 28 ]. Results presented in Figure 1 show a significant decrease in cell viability when both C6 and SH-SY5Y cells were exposed to 15 µM of Xn (C6: 100.0 ± 3.9 vs. 65.8 ± 3.1%, * p < 0.05; SH-SY5Y: 100.0 ± 4.7 vs. 77.8 ± 5.1%, * p < 0.05.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a study of the cell viability of C6 and SH-SY5Y cells in the presence of different concentrations of Xn was conducted in order to establish a proper concentration that has no severe toxicity to these cell lines. Previous results of our group showed no significant effect of 10 µM Xn in these cell lines; therefore, 5 and 15 µM Xn were tested [ 28 ]. Results presented in Figure 1 show a significant decrease in cell viability when both C6 and SH-SY5Y cells were exposed to 15 µM of Xn (C6: 100.0 ± 3.9 vs. 65.8 ± 3.1%, * p < 0.05; SH-SY5Y: 100.0 ± 4.7 vs. 77.8 ± 5.1%, * p < 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…The search for possible natural bioactive compounds that modulate the functionality of adenosine receptors could, therefore, be very helpful in the prevention and identification of new therapeutic molecules for AD. In that sense, previous work carried out in our group has shown that Xn causes a modulation at the level of gene expression of adenosine receptors in SH-SY5Y cells [ 28 ]. However, until now, it has not been fully reported how it could affect the adenosinergic pathway, including levels of these receptors in the membrane, functionality, or related enzymatic activities.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, the present study examined the possible involvement of adenosinergic signaling in the antitumoral action of RSV in human HeLa cervical carcinoma cells, as non-neural origin cells, and SH-SY5Y neuroblastoma cells, as a model of a neuronal-like cell. Ee have previously reported some regulatory mechanisms of adenosine receptors in both cell lines (42,43). desired concentration.…”
Section: Introductionmentioning
confidence: 99%